Internal Structures of the Developing Brain Assessed by HDlive Imaging - Florin Stamatian; Dan Boitor-Borza; Tunde Kovacs (Medical Network, 2016)
OBJECTIVES: The aim of this observational descriptive study of morphological research is to assess the nervous structures within the embryonic and early fetal brains not previously documented in literature by HDlive and Silhouette® modes. STUDY DESIGN: A total of 26 subjects were examined in vivo, i.e. 15 embryos and 11 fetuses in the first trimester of pregnancy (7 to 13 gestational weeks (GW)), using a transvaginal ultrasound using a Voluson E10, BT 15 scanner (GE Healthcare, Zipf, Austria). RESULTS: The clear visualization of the brain structures by HDlive rendering mode was possible in all 26 selected optimal volumes. The most representative images for each week of gestation are shown. At 7 GW the ultrasound semiology of the brain is simple. The choroid plexuses can be seen in the 4th ventricle at 8 GW and in the lateral ventricles at 9 GW by HDlive mode. At 9 GW the brain is developed enough so that the walls of the cerebral hemispheres, the ventricular system and the rhombic lips could be visualized by HDlive mode. At 10 GW we depicted the ganglionic eminences within the brain by HDlive mode. At 11 GW the thalamus was noticed. At 12 GW and 13 GW, HDlive images of choroid plexus asymmetry and choroid plexuses cysts are shown. CONCLUSION: The HDlive combined with Silhouette® mode can provide almost natural images of the internal structures of the embryonic and early fetal brain. Small-sized nervous structures such as the